2020
DOI: 10.1002/ijfe.1906
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tax preparers on corporate tax aggressiveness: Evidence form the UK context

Abstract: This paper studies the role of tax preparers in tax aggressiveness. Based on a sample of 342 UK companies indexed on the Financial Times Stock Exchange (FTSE) 350 from 2006 to 2016, it finds that external tax preparers are more tax aggressive than internal ones. The result is explained by the capability of external preparers to take more aggressive tax positions than internal preparers because of their knowledge in different changes to tax law, and their higher expertise in this field. The findings has implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Therefore, higher audit fees can be an indication of tax avoidance practices conducted by companies. This finding is supported by (Assidi& Hussainey, 2021) and (Ghifary et al, 2022). However, (Suyadnya&Supadmi, 2017) found that audit fees can reduce tax avoidance practices.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, higher audit fees can be an indication of tax avoidance practices conducted by companies. This finding is supported by (Assidi& Hussainey, 2021) and (Ghifary et al, 2022). However, (Suyadnya&Supadmi, 2017) found that audit fees can reduce tax avoidance practices.…”
Section: Introductionmentioning
confidence: 89%
“…In addition to political connections, audit fees can also influence tax avoidance actions (Hu, 2018;Salehi et al, 2020;Assidi& Hussainey, 2021;Ghifary et al, 2022); Suyadnya&Supadmi, 2017). Audit fees can be defined as the amount paid to external auditors by client companies for the services provided (Suwarno et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3.2 Variables' explanation and model specification 3.2.1 Dependent variable: effective tax rate. ETR is defined as the proportion of a firm's tax expenses compared to the accounting income before taxes (Assidi and Hussainey, 2021;DeZoort et al, 2018). This variable explains how firms behave in determining and paying the amount of the tax burden (Phillips, 2003).…”
Section: Research Methodology 31 Sample Descriptionmentioning
confidence: 99%
“…Second, in estimating corporate tax avoidance, we only used book–tax difference measures. Future analyses are encouraged to use other measures, such as ETRs (Ginesti et al , 2020; Assidi and Hussainey, 2021; Campa et al , 2021).…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%